1993
DOI: 10.1093/geronj/48.4.p189
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Response Selection and Noise Similarity on Age Differences in the Redundancy Gain

Abstract: We examined the impact of target redundancy for target-plus-noise (TPN) and target-only (TO) trials. Experiment 1 manipulated response selection load (two-choice vs go/no-go) and Experiment 2 (all two-choice) varied noise redundancy (single or cumulative noise letters) on a visual search, divided attention task in which target letters were presented in one, two, or three corners of a four-corner display. Half of the trials also included noise letters. For Experiment 1, there was a definite redundancy gain for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
15
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 0 publications
10
15
0
Order By: Relevance
“…We therefore tested participants using a complex task that required either the conjoining of target features (Experiment 1) or the division of attention between spatial locations (Experiment 2). Consistent with our predictions and prior literature (e.g., Allen et al, 1992Allen et al, , 1993Allen et al, , 1994Bucur et al, 2005), the absolute magnitude of the RSE was significantly larger for the older adults than for the younger adults in both of the present experiments. In Experiment 1, this difference did not remain significant after we used a proportional measure to control for the overall slower responses of the older adults.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We therefore tested participants using a complex task that required either the conjoining of target features (Experiment 1) or the division of attention between spatial locations (Experiment 2). Consistent with our predictions and prior literature (e.g., Allen et al, 1992Allen et al, , 1993Allen et al, , 1994Bucur et al, 2005), the absolute magnitude of the RSE was significantly larger for the older adults than for the younger adults in both of the present experiments. In Experiment 1, this difference did not remain significant after we used a proportional measure to control for the overall slower responses of the older adults.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with Allen et al (1992Allen et al ( , 1993Allen et al ( , 1994, Bucur et al also found evidence for an agerelated increase in the absolute magnitude of the RSE. The Age Group × Redundancy interaction, however, did not remain significant after correcting for generalized slowing.…”
Section: Redundancy Gain and Coactivation In Older Adultsmentioning
confidence: 69%
“…Given that advancing age is accompanied by a reduction in central resources (Allen et al, 1993), while leaving automatic processes intact (Hasher and Zacks, 1979), this finding accords with the idea that hand-cues prompt the fast, bottom-up selection and preparation of fingers, whereas the more difficult finger-and neither-cues require slow and effortful top-down processes to establish a selective preparatory set.…”
Section: Introductionsupporting
confidence: 78%
“…According to the resource allocation/uncertainty reduction approach, the substantial aging effect for the finger-cued and neither-cued conditions and the relative absence of such an effect for the hand-cued condition might be attributed to the notion that advancing age is accompanied by a reduction in attentional resources (e.g., Allen, Groth, Weber, & Madden, 1993;Salthouse, 1988), although automatic processes are left intact (e.g., Hasher & Zacks, 1979;Hoyer & Plude, 1980). Of course, extensive investigations are needed to examine the validity of these speculations, but at least two alternative interpretations of the hand-cued advantage can be dismissed.…”
Section: Discussionmentioning
confidence: 99%